Long noncoding RNA MRAK009713 is a novel regulator of neuropathic pain in rats. Issue 10 (October 2017) - Li, Guilin; Jiang, Huaide; Zheng, Chaoran; Zhu, Gaochun; Xu, Yurong; Sheng, Xuan; Wu, Bing; Guo, Jingjing; Zhu, Shuanghua; Zhan, Yuting; Lin, Weijian; Ding, Rui; et al.
Abstract : Abstract: Long noncoding RNAs have been implicated in neuropathy. Here, we identify and validate a long noncoding RNA, MRAK009713, as the primary regulator of neuropathic pain in chronic constriction injury (CCI) rats. MRAK009713 expression was markedly increased in CCI rats associated with enhanced pain behaviors, and small interfering RNA against MRAK009713 significantly reduced both mechanical and thermal hyperalgesia in the CCI rats. MRAK009713 is predicted to interact with the nociceptive P2X3 receptor by CatRAPID, a bioinformatics technology. Overexpression of MRAK009713 markedly increased expression of P2X3 in the dorsal root ganglia of the control rats, and MRAK009713 small interfering RNA significantly inhibited the P2X3 expression in the dorsal root ganglia of the CCI rats. MRAK009713 directly interacted with the P2X3 protein heterologously expressed in the human embryonic kidney (HEK) 293 cells and potentiated P2X3 receptor function. Thus, MRAK009713 is a novel positive regulator of neuropathic pain in rats through regulating the expression and function of the P2X3 receptor. Abstract : MRAK009713 overexpression enhanced pain behaviors and P2X3 expression in the DRG of control rats. MRAK009713 siRNA reduced hyperalgesia and P2X3 expression in the DRG of CCI rats.